SENSITIVITY AND SENSING OF SOIL GAS RADON POLLUTION IN CERTAIN AREAS OF THE PROVINCE OF SALAHIDIN USING CR-39 DETECTOR - AHMED MOHAMMED OBAID (مجلة جامعة الانبار للعلوم الصرفة, 2013)
In this search Four samples have been selected for determine [Radon gas] concentration . these samples distributed to Four regions known as ( Baiji District – communication station, Derbonat Algezo–Dholoiya region [-] Balad District, Tikrit District [-] Hammad Shihab communication station, Samarra District – Qadisiaya branch). The aim of this study is to determine the concentration of Radon gas in these samples, by using CR-39 detector as a remote sensing technique .The results showing that we are fined there is increasing in Radon gas level within the values (17.86 x103 – 24.14 x103) Bq.m-3 above of the natural level (7.2 x103 ) Bq.m-3. This increasing may be due to using of penetrating ammunition containing depleted uranium.